ON THE CORRECTNESS OF DIFFERENTIAL AND DIFFERENCE METHODS FOR ANALYSIS OF THE STABILITY OF CONTINUOUS RAILWAYS (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1991)
The problem of the rail ways stability exists for a long time and there are about 100 theoretical methods to solve it. In this paper the connection between differential and difference methods is discussed.